BARRIERS OF EXTERNAL ECONOMIC ACTIVITIES TO RUSSIAN NON-COMMODITY EXPORTS - E. A. Amiraslanova; N. Yu. Barkova; T. O. Shpunt (Вестник университета)
The non-commodity exports development issues from the Russian Federation to foreign countries have been considered. The main barriers, constraining the development of non-commodity exports have been analyzed. Also the classification of such “barriers of ignorance” has been developed and the measures, allowing to reduce the impact of these barriers have been proposed: creation of an electronic commercial site; creation of multifunctional centers, in which certification and licensing procedures would be carried out, customs and tax сonsultancy to potential exporters, advice and assistance in obtaining the necessary permission documentation in foreign countries; сounselling on the correct execution of foreign economic contracts to avoid double taxation and transfer pricing and other measures.